The work of Knud Rasmussen in the Canadian Arctic as described by RCMP Inspector Stuart Wood - Treude, Erhard (Études/Inuit/Studies, 2004)
AbstractA detailed report which the RCMP officer at Herschel Island forwarded to his superiors in Edmonton after Knud Rasmussen had passed through, during the Fifth Thule Expedition, is reproduced here verbatim. Even though the text is not in Rasmussen's own words, it appears to usefully complement and expand the existing picture of him as a researcher. It, at the same time, also reveals some undeniable flaws.